PENGARUH MODEL PEMBELAJARAN DAN JENIS PENILAIAN FORMATIF TERHADAP HASIL BELAJAR IPA SISWA SMPN - Ni Ketut Rapi (Jurnal Cakrawala Pendidikan, 2016)
Abstrak: Penelitian bertujuan untuk mendeskripsikan perbedaan hasil belajar IPA antara siswa yang mengikuti model pembelajaran inkuiri dan model pembelajaran konvensional, perbedaan hasil belajar IPA antara siswa yang mengikuti pembelajaran dengan PBK dan pembelajaran dengan penilaian konvensional, dan pengaruh interaksi antara model pembelajaran dan jenis penilaian formatif terhadap hasil belajar IPA. Penelitian ini menggunakan metode eksperimen semu. Populasi penelitian adalah siswa kelas VII SMPN Singaraja pada semester ganjil tahun ajaran 2015/2016 sebanyak 2398 siswa. Pengambilan sampel dilakukan dengan teknik multi stage, jumlah sampel 120 siswa. Instrumen pengumpulan data menggunakan tes bentuk objektif, dengan reliabilitas tes = 0,8770, sedang analisis data menggunakan teknikanava dua jalur. Hasil penelitian ini menunjukkan: 1) terdapat perbedaan hasil belajar IPA antara siswa yang mengikuti model pembelajaran inkuiri dan model pembelajaran konvensional, 2) terdapat perbedaan hasil belajar IPA antara siswa yang diberi penilaian berbasis kelas dan yang diberi penilaian konvensional, terdapat pengaruh interaksi antara model pembelajaran dan jenis penilaian formatif terhadap hasil belajar IPA. Kata kunci: model pembelajaran, jenis penilaian formatif, hasil belajar IPATHE INFLUENCE OF THE TEACHING MODEL AND THE FORMATIVE EVALUATION TYPE ON THE STATE JUNIOR HIGH SCHOOL STUDENTS’ SCIENCE LEARNING ACHIEVEMENT Abstract: The objectives of this study were 1) to describe the difference in the Science learning achievement between the students taught using the inquiry teaching model and those taught using the conventional teaching model; 2) to describe the difference in the Science learning achievement between the students joining the teaching with class-based evaluation and those joining the teaching with the conventional evaluation; and 3) to describe the influence of the interaction between the teaching model and the formative evaluation type on the Science learning achievement. This study used the quasi experimental design. The population was grade VII students of state junior high schools in Singaraja in the odd semester of 2015/2016 academic year consisting of 2,398 students. The sample consisting of 120 students was drawn using the multi-stage sampling technique. The data were collected using the objective test, with the reliability coefficient of 0.8770. The data were analyzed using the two-way anova. The findings showed that: 1) there was a significant difference in the Science learning achievement between the students joining the inquiry teaching model and those joining the conventional teaching model; 2) there was a significant difference in the Science learning achievement between the students given the class-based evaluation and those given the conventional evaluation; and 3) there was an influence of the interaction between the teaching model and the formative evaluation type on the Science learning achievement. Keywords: teaching model, formative evaluation type, Science learning achievement